Text-to-speech synthesis in computer-assisted language learning for Irish : development and evaluation - Ní Chiaráin, Neasa (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2014)
This thesis sets out to develop and evaluate speech synthesis-based computer-assisted language learning (CALL) platforms. Central to this work is the evaluation of the fitness- for-purpose, as part of a language teaching/learning facility, of the text-to-speech (TTS) Irish language synthesis system that these platforms employ. The TTS system in question has been developed by the ABAIR project at Trinity College, Dublin and is being extended and improved on an ongoing basis.
Keywords: Phonetics, Ph.D.; Ph.D. Trinity College Dublin